Comparison of matrix metalloproteinase-13 and tissue inhibitor of metalloproteinase-1 levels and alveolar bone density in chronic periodontitis before and after scaling and root planning - Aini Hariyani Nasution; Lidya Irani Nainggolan; Widianto Meydhyono (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Periodontitis is typically associated with disorders characterized by compromised tooth-supporting tissue. Damage to periodontal tissue is caused by an imbalance between matrix metalloproteinases and their inhibitors. Decreased tissue inhibitor and elevated matrix metalloproteinase levels result in collagen connective tissue and bone degradation. Several studies have shown that high levels of matrix metalloproteinase-13 (MMP-13) and low levels of tissue inhibitor of metalloproteinase-1 (TIMP-1) are also found in gingival crevicular fluid and saliva of patients with periodontitis. The purpose of this study was to determine the comparison of MMP-13 levels, TIMP-1 levels of saliva and bone density in patients with chronic periodontitis before and after scaling and root planning (SRP). The study samples were selected from patients who came for treatment at the Periodontics Installation of Universitas Sumatera Utara. A total of 16 patients were selected (n = 16) with a diagnosis of chronic periodontitis. The result showed that salivary MMP-13 levels in chronic periodontitis patients before SRP were higher than salivary MMP-13 levels after SRP and the difference was statistically significant (p < 0.05). It was also revealed that salivary TIMP-1 levels and alveolar bone density in chronic periodontitis patients before SRP were lower than that after SRP and the difference was statisticallysignificant (p < 0.05). There was a positive correlation between clinical parameters and salivary MMP-13 levels in patients with chronic periodontitis before and after SRP, but it was not statistically significant (p > 0.05). There was a negative correlation between clinical parameters and salivary TIMP-1 levels in patients with chronic periodontitis before and after SRP, but it was not statistically significant (p > 0.05).